Synthetic epistemology and ontology - Dumouchel, Paul (Mechane, 2021)
The synthetic methodology is often presented as “understanding by building”. The question I wish to ask is: what does it reveal about the world in which we live that essential cognitive gains can be made by building? Alternatively, what would it mean to live in world where no such gain was possible? That is to say, in a world in which building was the mere application of preexisting knowledge. In a sense we know that world quite well because many philosophers and scientists, pasts and presents, have argued that thist is the world in which we do live. How is the world in which essential cognitive gains can be had from building different from a world where no such gain is possible? If it is the case that we live in a world where (essential) cognitive gains can be made by building, this, I will argue, has important consequences for our concept of ‘model’ and the partial revision of the epistemic role of model that follows will lead me to adduce to some of the other questions especially concerning the normative dimension of synthetic methodology.